Tarekat sebagai Media Bimbingan Konseling (Studi Tarekat Qodiriyah Naqsabandiyah Pondok Pesantren Suryalaya) - M. Mardjun, Maghfirah (Edukasi: Journal of Educational Research, 2022)
The physical, psychological, and spiritual burdens that must be faced by modern humans are very large, resulting in an outbreak of anxiety and anxiety. To be able to obtain peace in life, the salik (practicers of Sufism) formed halaqoh-halaqoh which later became known as the tarekat. It is through this tarekat that the dervishes take the salik starling with the help of a teacher (mursyid) in order to gain a balance of soul and heart. Based on this, this study is intended to find out how the concept offered by the Qodiriyyah Naqshabandiyyan Tarekat Pondok Pesantren Suryalaya, as spiritual khalaqoh in providing counseling guidance to a salik in particular and society in general. The method used in this study is a qualitative method with a phenomenological approach. This study found that the counseling guidance carried out at the Tarekat adiriyyah Naqsbandiyyah Pondok Pesantren Suryalaya by Habib Idan is a counseling guidance that has a Sufistic style.